PENGARUH MODEL PEMBELAJARAN PROJECT BASED LEARNING (PJBL) TERHADAP HASIL BELAJAR SISWA MELALUI KEMAMPUAN KOLABORATIF DI KELAS VII UPTD SMP N 5 PEMATANGSIANTAR T.A 2025/2026 - Melda Fronika Sihombing; Susy Alestriani Sibagariang; Anggun Tiur Ida Sinaga (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Project Based Learning (PjBL) model, specifically the Group Project type, on students’ Social Studies learning outcomes through collaborative ability as an intervening variable among seventh-grade students of UPTD SMP Negeri 5 Pematangsiantar in the academic year 2025/2026. This research employed a quantitative approach using a quasi-experimental design with a pretest-posttest control group design. The population of this study consisted of all seventh-grade students of UPTD SMP Negeri 5 Pematangsiantar. The samples were class VII-4 as the experimental class and class VII-3 as the control class. The research instruments included learning outcome tests (pre-test and post-test) and a collaborative ability questionnaire. Data analysis techniques included normality tests, homogeneity tests, and hypothesis testing using t-tests and regression analysis.The results showed that the Project Based Learning (PjBL) model had a significant effect on students’ collaborative ability. Furthermore, there was a significant effect of the Project Based Learning (PjBL) model on students’ Social Studies learning outcomes. Collaborative ability also significantly influenced students’ learning outcomes. Therefore, the Project Based Learning (PjBL) model has both direct and indirect effects on learning outcomes through collaborative ability.Based on these findings, it can be concluded that the implementation of the Project Based Learning (PjBL) model of the Group Project type is effective in improving collaborative ability and Social Studies learning outcomes of seventh-grade students at UPTD SMP Negeri 5 Pematangsiantar.